IMAGE SEGMENTATION USING EFCM FOR BANANA STEM DISEASE IDENTIFICATION (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Image Segmentation is the interaction by which an advanced image is dividedinto different subgroups (of pixels) called Image Objects, which can diminish the intricacy of theimage, and accordingly examining the image gets less difficult. This paper portrays anotherautomatic image segmentation methodology for segmenting plants. This paper presentsstraightforward methodology towards plant growth analysis Enhanced Fuzzy C- Meansclustering algorithm is utilized to segment the region of interest, morphological shape analysis isapplied to the Image Segmentation for Banana Plant. The strategy is highly promising nearbyaccuracy agriculture when we have large area to monitor.